2018
DOI: 10.1007/s10528-018-9855-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tumor Necrosis Factor Alpha-Induced Protein 3 Interacting Protein 1 (TNIP1) Gene Polymorphism (rs7708392) with Lupus Nephritis in Egyptian Patients

Abstract: Lupus nephritis (LN) is a major cause of morbidity and mortality in systemic lupus erythematosus (SLE). Previous studies suggest that mutant A20 binding inhibitor of NF-κB 1 (ABIN1) protein encoded by tumor necrosis factor alpha-induced protein 3 interacting protein 1 (TNIP1) gene is associated with LN via NF-κB dysregulation. The aim of the current study was to evaluate the association of TNIP1 gene SNP rs7708392 with SLE and LN in Egyptian patients. 5' nuclease Allelic discrimination was used to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The most reported TNIP1 variant associated with SLE and LN is rs7708392. This SNP has been replicated in several different SLE cohorts including European and Chinese, 16 17 North American, 18 Egyptian, 19 Japanese, 20 Swedish 21 and Hispanic 22 populations. Our group found a strong association for rs7708392 with LN in European Americans (EA) in a large-scale study of North American patients with SLE.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The most reported TNIP1 variant associated with SLE and LN is rs7708392. This SNP has been replicated in several different SLE cohorts including European and Chinese, 16 17 North American, 18 Egyptian, 19 Japanese, 20 Swedish 21 and Hispanic 22 populations. Our group found a strong association for rs7708392 with LN in European Americans (EA) in a large-scale study of North American patients with SLE.…”
Section: Introductionmentioning
confidence: 80%
“… 20 A study of a Egyptian cohort that included 53 SLE patients with LN, 57 SLE patients without nephritis and 85 healthy controls showed that rs7708392 was significantly more prevalent among patients with LN than in patients without LN. 19 However, there are discrepancies as to which allele of rs7708392 is associated with increased risk. Our group identified the minor C allele to be associated with increased risk for LN in North American patients with SLE with European ancestry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relations among polymorphisms of several inflammatory regulatory genes, such as STAT4 , TNF‐α‐Induced Protein 3 Interacting Protein 1 ( TNIP1 ), Interferon regulatory factor 5 ( IRF5 ), interleukin‐10 promoter, TNF‐α Promoter and SLE were conducted. We evaluated the effect of COX‐2 rs2745557 gene polymorphism on SLE.…”
Section: Discussionmentioning
confidence: 99%
“…The TNIP1 rs3792783 SNP, located in an intronic region, has been previously associated with antibody-positive primary Sjögren’s syndrome [36] and systemic sclerosis [40], and seems to be a risk factor for Vogt–Koyanagi–Harada syndrome [41]. Also, the TNIP1 rs7708392 SNP, also located in an intronic region of TNIP1, has been related to a higher risk of developing lupus nephritis [42,43], lupus erythematosus [44,45,46], autoimmune hepatitis [47], and Sjögren’s syndrome [36]. Among septic patients, this is the first study investigating the role of TNIP1 SNPs on this disease.…”
Section: Discussionmentioning
confidence: 99%